CH4 activation by PtX+ (X = F, Cl, Br, I) - Zhao, Jin; Qi, Lingxi; Li, Wenzuo; Cheng, Jianbo; Li, Qingzhong; Liu, Shaoli (Frontiers in Chemistry, 2022)
Reactions of PtX+ (X =F, Cl, Br, I) with methane have been investigated at the density functional theory (DFT) level. These reactions take place more easily along the low-spin potential energy surface. For HX (X =F, Cl, Br, I) elimination, the formal oxidation state of the metal ion appears to be conserved, and the importance of this reaction channel decreases in going as the sequence: X = F, Cl, Br, I. A reversed trend is observed in the loss of H2 for X = F, Cl, Br, while it is not favorable for PtI+ in the loss of either HI or H2. For HX eliminations, the transfer form of H is from proton to atom, last to hydride, and the mechanisms are from PECT to HAT, last to HT for the sequence of X = F, Cl, Br, I. One reason is mainly due to the electronegativity of halogens. Otherwise, the mechanisms of HX eliminations also can be explained by the analysis of Frontier Molecular Orbitals. While for the loss of H2, the transfer of H is in the form of hydride for all the X ligands. Noncovalent interactions analysis also can be explained the reaction mechanisms.